Intraepithelial corneal deposits associated with Mirvetuximab soravtansine use for platinum-resistant ovarian cancer - Charlotte McRae; Rachael Cowan; Macy Green; Jack S. Parker (American Journal of Ophthalmology Case Reports)
Purpose: Present a case of Mirvetuximab soravtansine (MIRV)-induced intraepithelial corneal deposits, review a proposed mechanism to explain the blurred vision our patient experienced, and explain clinical exams that may be used to support the diagnosis. Observations: A 63-year-old female with metastatic ovarian cancer diagnosed with intraepithelial corneal deposits two weeks after her first MIRV infusion. Treatment with topical prednisolone acetate 1 % ophthalmic suspension and lubricating eye drops without interruption of her MIRV infusions resulted in complete resolution of blurry vision and corneal deposits. Conclusions and importance: The natural reversibility of MIRV-induced keratopathies underscores the need for prompt and regular ophthalmic assessments throughout drug administration. Understanding the mechanism behind these corneal changes, how to recognize them in a clinical setting, and expedite their reversal are essential to improve quality-of-life metrics in patients receiving MIRV transfusions.